2014
DOI: 10.1002/ijc.28984
|View full text |Cite
|
Sign up to set email alerts
|

Long-term HPV type-specific risks for ASCUS and LSIL: A 14-year follow-up of a randomized primary HPV screening trial

Abstract: Human papillomavirus (HPV) infections result in a significant burden of low-grade cervical lesions. Between 1997 and 2000, our randomized trial of primary HPV screening enrolled 12,527 women participating in population-based screening. Women between 32 and 38 years of age (median: 34, interquartile range: 33-37) were randomized to HPV and cytology double testing (intervention arm, n 5 6,257 enrolled, n 5 5,888 followed-up) or to cytology, with samples frozen for future HPV testing (control arm, n 5 6,270 enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 22 publications
(40 reference statements)
3
17
2
Order By: Relevance
“…These results are consistent with those of Lu et al in Beijing [28] and the study on Chinese women in 2013 which showed that 71.4% of HR-HPV positive CIN2+ cases were attributable to HPV16 or 18 [29]. A 14-year follow-up study in Sweden presented HPV16 and 31 as contributing to higher incidences of CIN2+ [1130]. …”
Section: Discussionsupporting
confidence: 90%
“…These results are consistent with those of Lu et al in Beijing [28] and the study on Chinese women in 2013 which showed that 71.4% of HR-HPV positive CIN2+ cases were attributable to HPV16 or 18 [29]. A 14-year follow-up study in Sweden presented HPV16 and 31 as contributing to higher incidences of CIN2+ [1130]. …”
Section: Discussionsupporting
confidence: 90%
“…In contrast, nonvaccine HPV types HPV 33, 51, 52, 56, 59 and 66 were more common in our study than in the prevaccination cohort . HPV 31, 35 and 45 were more prevalent in CIN2‐3 cases, while HPV 39, 42, 68 and 90 were more common only among CIN1 cases when compared to the prevaccination data (Table ) …”
Section: Resultscontrasting
confidence: 74%
“…We observed that the HPV DNA prevalence of vaccine‐targeted types was much lower than the population‐based prevalence of HPV DNA genotypes in Sweden during the prevaccination era (Table ) . None of all tested samples ( n = 367) contained the vaccine types HPV 6 or 11 (data not shown).…”
Section: Resultsmentioning
confidence: 87%
“…The frequency of this genotype distribution is quite similar to that found in another Cobas PCR study for ASC-US [38]. According to some authors, a predominance of HPV-16 and -18 genotypes does not necessarily occur in ASC-US, and subtype variability is expected [39]. …”
Section: Discussionsupporting
confidence: 63%